Research on Deterministic Ring Removal Method for Full-Aperture Double-Sided Polishing of Large Aperture Optical Components - Yifan Bai; Bo Xiao; Chunyang Wang; Ke Chen; Linzhe Deng; Siling Huang; Xuelian Liu (IEEE Photonics Journal)
To address the issues in polishing medium and large aperture optical components, which are reliant on the personal experience of processing personnel and exhibit poor controllability, this study conducted a comprehensive examination of the polishing process for these planar optical components. This article constructs a processing prediction model for large-diameter ring pendulum double-sided polishing equipment. Based on this, a simulation of the theoretical removal amount distribution of ring-pendulum double sided polishing was conducted to ascertain the relationship between various process parameters and their impact on the surface removal amount distribution of the component. Based on the obtained relationship, a decision support system for the process parameters of ring-pendulum double sided polishing was developed, which achieved the deterministic removal of rings in medium and large aperture planar optical components and reduced the dependence of ring pendulum double-sided polishing on the personal experience of process decision-makers. After experimental verification, the characteristics of the simulation results of the processing prediction model were consistent with the actual processing results. The developed process parameter decision assistance system was used to make process parameter decisions for two 430 * 430 mm fused quartz components, achieving the removal of the target ring of the components. The surface figure accuracy of the two components has been processed from 3.09λ and 3.5λ to 1.53λ and 1.79λ, respectively.